2020
DOI: 10.1002/anie.202003050
|View full text |Cite
|
Sign up to set email alerts
|

Diborane(4) Azides: Surprisingly Stable Sources of Transient Iminoboranes

Abstract: Herein we describe the first examples of isolable electron‐precise diboranes(4) that bear azide moieties: the acyclic 1,2‐diazido‐1,2‐bis(dimethylamino)diborane(4) and the cyclic 1,4‐diaryl‐2,3‐diazido‐1,4‐diaza‐2,3‐diborinines (aryl=mesityl, 2,6‐xylyl, 4‐tolyl). The reported examples are not only stable enough to be observed and isolated (putative transient diborane(4) azides previously reported by our group spontaneously decompose even below room temperature), but some of them are even robust enough to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 125 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…The spontaneous decomposition of borole azide 2 well below room temperature is unusual for boron azides and is akin to the high reactivities observed for the putative diborane(4) azides that are not stabilized by π-donating substituents. 37,38 It is also in stark contrast with the reactivity of azidoborafluorene ( II , see Fig. S56 and S57, ESI†) reported by Bettinger et al 39,40 Indeed, II can be isolated at room temperature and is reported to undergo azide-decomposition upon heating in refluxing heptane to form oligomers of the hypothetical BN-phenanthryne, a cyclic iminoborane.…”
mentioning
confidence: 85%
“…The spontaneous decomposition of borole azide 2 well below room temperature is unusual for boron azides and is akin to the high reactivities observed for the putative diborane(4) azides that are not stabilized by π-donating substituents. 37,38 It is also in stark contrast with the reactivity of azidoborafluorene ( II , see Fig. S56 and S57, ESI†) reported by Bettinger et al 39,40 Indeed, II can be isolated at room temperature and is reported to undergo azide-decomposition upon heating in refluxing heptane to form oligomers of the hypothetical BN-phenanthryne, a cyclic iminoborane.…”
mentioning
confidence: 85%
“…Since azides are known both to insert as nitrene moieties into B-B bonds [22][23][24][25][26] and undergo copper-catalysed click reactions with alkynes, [27][28][29][30][31] the reaction of 1 TMS with arylazides was studied. Independent of the stoichiometry, the reaction temperature, the electronic effect (+I, −I, +M, −M) of the N-aryl substituent or the addition of a typical Huisgen cycloaddition copper catalyst (CuOTf, CuI, [(MeCN) 4 Cu]OTf, [(MeCN) 4 Cu] BF 4 , ((EtO) 3 P)CuI), the bis(aminoboryl)arylamine product 2 TMS -Ar (Ar = Ph, pTol (4-MeC 6 H 4 ), Ph CF3 (4-CF 3 C 6 H 4 ), Ph OMe (4-OMeC 6 H 4 ), Ph CN (4-CNC 6 H 4 )) was obtained as a colourless solid in good to excellent isolated yield (63-89%, Scheme 2).…”
Section: Reactions With Azidesmentioning
confidence: 99%
“…Unlike complexes 1-L, which all show a major UV-vis absorption band in the 270-320 nm range, the UV-vis spectrum of 3-DMAP shows four distinct absorption bands at 264 nm (λ max ), 290 nm, 325 nm and 404 nm, the latter covering the 370-450 nm range and accounting for the green colour of Although one crystallisation batch of 3-DMAP also contained a few crystals of the 1-DMAP isomer, which were characterised by X-ray crystallography, the latter was never formed in sufficient quantities to be detectable by NMR spectroscopy, even when the reaction was carried out at low temperature. While azide-substituted diboranes have recently been isolated for the first time, 53 1-L, 2 and 3-L are, to our knowledge, the first examples of isolable diazenidodiboranes. X-ray diffraction analyses were performed on single crystals of 1-L (L = SMe 2 , PMe 3 , PCy 3 , CNMes*, DMAP), 2 and 3-DMAP (Fig.…”
mentioning
confidence: 91%
“…Although one crystallisation batch of 3-DMAP also contained a few crystals of the 1-DMAP isomer, which were characterised by X-ray crystallography, the latter was never formed in sufficient quantities to be detectable by NMR spectroscopy, even when the reaction was carried out at low temperature. While azide-substituted diboranes have recently been isolated for the first time, 53 1-L , 2 and 3-L are, to our knowledge, the first examples of isolable diazenidodiboranes.…”
mentioning
confidence: 91%